Pan-sharpening using a guided filter. Issue 8 (17th April 2016) - Liu, Junmin; Liang, Shunlin
ABSTRACT: Pan-sharpening aims to integrate the spatial details of a high-resolution panchromatic (Pan) image with the spectral information of low-resolution multispectral (MS) images to produce high-resolution MS images. The key is to appropriately estimate the missing spatial details of the MS images while preserving their spectral contents. However, many existing methods extract the spatial details from the Pan image without fully considering the structures of the MS images, resulting in spectral distortion due to redundant detail injection. A guided filter can transfer the structures of the MS images into the intensity component or the low-pass approximation of the Pan image. Using the guided filter, we propose two novel pan-sharpening methods to reduce the redundant details among the MS and Pan images. Specifically, we extract the missing spatial details of the MS images by minimizing the difference between the Pan image and its corresponding filtering output, with the help of the MS images. Two different ways of using the MS images as guided images lead to two proposed methods, which can be grouped into component substitution (CS) family. Extensive experimental results over three data sets collected by different satellite sensors demonstrate the effectiveness of the proposed methods.